Stuck mitral prosthesis in pregnancy - A challenge - Pankaj K Gupta; Indira Malik; A S Tomar; Vishnu Datt; Sanjula Virmani; Vithal K Betigeri (Wolters Kluwer Medknow Publications, 2017)
Pregnancy with prosthetic valve is a challenging situation since this is a hypercoagulable state and maintenance of anticoagulation for prosthetic valves becomes difficult due to the teratogenic effects and altered pharmacokinetics of anticoagulant drugs. This may result in prosthetic valve thrombosis which is an emergency and requires multidisciplinary approach for management. We present a case of a patient who presented with thrombosed mitral prosthesis at 34 wks of gestation; after a multispeciality consultation, she eventually underwent caesarean section followed by mitral valve replacement.